KUALITAS SPERMATOZOA AYAM PERANAKAN SENTUL DALAM PENGENCER RINGER LAKTAT KUNING TELUR DENGAN BERBAGAI MONOSAKARIDA (Quality of Sentul Crossbreed Chicken Spermatozoa in Ringer Lactate-Egg Yolk Diluents Supplemented with Various Monosaccharide) - Khaeruddin Khaeruddin; Raden Iis Arifiantini; Cece Sumantri; Sri Darwati (Jurnal Kedokteran Hewan, 2016)
The aim of this study was to examine the preservation of sentul crossbreed chicken semen in ringer lactate egg yolk diluent supplemented with various monosaccharide. Semen was collected from three roosters using massage method. Immediately after collection, the semen was evaluated macroscopically and microscopically. Semen with more than 70% motility was divided into four tubes. Each of them diluted with ringer lactate egg yolk glucose (RLEYG), ringer lactate egg yolk fructose (RLEYF), ringer lactate egg yolk xylose (RLEYX) and ringer lactate egg yolk mannose (RLEYM). Semen was stored in refrigerator (5o C) for sixty hours and evaluated every twelve hours for spermatozoa motility and viability. Results showed that no significant difference (P0.05) among diluents used on spermatozoa quality parameters after dilution and during preservation. Semen quality decrease during storage and at sixty hours of storage, the motility and viability of spermatozoa ranging from 48.33±2.56 to 55.42±2.26% and 58.59±2.87 to 64.83±2.42%, respectively. This research conclude that glucose, fructose, xylose and mannose can be used as energy source for roosters semen during preservation.